COGNITIVE IMPAIRMENT AND ITS ASSOCIATED FACTORS AMONG GERIATRIC POPULATION IN A DAYCARE CENTER OF KOLKATA - Abhik Sinha (Ageing and society: The Indian journal of gerontology, 2013)
Cognitive impairment is an important issue for the geriatric population . Growing population of geriatric age group is now a concern for both developed and developing countries . The geriatric population in India which was 7.7% in 2001 has increased up to nearly 8.14% in 2011 and is expected to go up to 8.94% in 2016 .In this context the study was planned with the objectives of to find out the level of cognitive impairment in the study population and to assess the sociodemographic profile of the study population . This was a cross sectional descriptive study done in the day care centres of Calcutta Metropolitan Institute of Gerontology (CMIG). There were total 100 inmates in the two day care centres under CMIG in Kolkata which constituted the study population . The duration of the study was for 3 months (September to November 2014). In the present study 6 % of the geriatric population under study were found to have cognitive impairment .Moderate and severe cognitive impairment were absent in the study population .MMSE score was found to be unrelated with gender .Hypertension and diabetes were found to be the significant predictors of the MMSE score in the study population .